Bimetal catalyst as well as preparation method and application thereof

By designing bimetallic catalysts in ore dressing wastewater treatment and synthesizing nano-zinc sulfide/molybdenum sulfide heterostructures by solvothermal method, the problem of low treatment efficiency of traditional Chinese phalal wastewater in the prior art was solved, and efficient visible photocatalytic degradation effect was achieved.

CN119680584APending Publication Date: 2025-03-25XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411851043.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to thoroughly treat ore-dressing yellow medicine wastewater, traditional water treatment methods have problems such as high economic costs, and the activity and photoresponse characteristics of the photocatalytic oxidation method are insufficient.

Method used

By ion exchange of ammonium molybdate, sulfur source powder and zinc acetate, a bimetallic catalyst was formed, and nano-zinc sulfide/molybdenum sulfide heterostructure was synthesized by solvothermal method to improve its photoresponse characteristics and catalytic activity.

Benefits of technology

It has achieved efficient degradation of yellow medicine wastewater under visible light, with a catalytic rate twice that of single zinc sulfide, which is of great significance to the green development of mines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680584A_ABST
    Figure CN119680584A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgy, and discloses a bimetallic catalyst and a preparation method and application thereof.The method comprises the steps that ammonium molybdate, sulfur source powder and zinc acetate are added into a solvent to be mixed, molybdenum ions and zinc ions are subjected to ion exchange, and a suspension A is obtained; the mass ratio of the ammonium molybdate to the sulfur source powder to the zinc acetate is 1: (3-5): (1-3); the ratio of the total mass of the ammonium molybdate, the sulfur source powder and the zinc acetate to the mass volume of the solvent is (1.1-2.2): 50, and the unit is g / mL; adjusting the suspension A to be weakly acidic, and then adding a surfactant for activation to obtain a solution A; carrying out hydrothermal reaction on the solution A to obtain a suspension B; and carrying out solid-liquid separation, washing and drying on the suspension B to obtain the bimetallic catalyst. Two different metals are coupled, and the obtained bimetallic catalyst is high in activity and good in light response characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a bimetallic catalyst and a preparation method and application thereof. Background Art

[0002] Xanthate and its derivatives are the most commonly used collectors in the flotation of sulfide ores and oxide ores. In recent years, the use of collectors has increased. If the wastewater is discharged directly without treatment during the mineral processing process, it will pollute the water, soil and even the air around the mine, and even endanger human health. Therefore, it is of great significance to use some technical means to effectively treat the mineral processing xanthate wastewater and purify the mine water environment for the green development of mines.

[0003] At present, it is difficult to completely treat xanthate wastewater with a single traditional water treatment method, and the combination of multiple treatment processes has problems such as high economic cost. Photocatalytic oxidation has attracted widespread attention due to its advantages such as simple equipment and the ability to use sunlight to degrade most organic pollutants in wastewater. It is of practical significance to design a new photocatalyst with high activity and good light response characteristics for mineral processing wastewater. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a bimetallic catalyst and a preparation method and application thereof. The present invention couples two different metals, and the obtained bimetallic catalyst has high activity and good light response characteristics.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a bimetallic catalyst comprises the following steps: Ammonium molybdate, sulfur source powder and zinc acetate are added to a solvent and mixed to allow molybdenum ions and zinc ions to undergo ion exchange to obtain a suspension A; the mass ratio of ammonium molybdate, sulfur source powder and zinc acetate is 1:(3-5):(1-3); the mass volume ratio of the total mass of ammonium molybdate, sulfur source powder and zinc acetate to the solvent is (1-1.4):50, in g / mL; The suspension A is adjusted to be weakly acidic, and then a surfactant is added for activation to obtain a solution A; The solution A is subjected to a hydrothermal reaction to obtain a suspension B; The suspension B is subjected to solid-liquid separation, washing and drying to obtain the bimetallic catalyst.

[0006] Preferably, the solvent is a solution of ethylene glycol and deionized water mixed in equal volumes.

[0007] Preferably, after adding ammonium molybdate, sulfur source powder and zinc acetate into a solvent and mixing, the following process is also included: Ultrasonication was performed at an ultrasonic power of 60-80 W for 10-20 min, and then magnetic stirring was performed for 1-3 h to obtain a suspension A.

[0008] Preferably, the sulfur source powder is thioacetamide.

[0009] Preferably, the suspension A is adjusted to be weakly acidic, and then a surfactant is added for activation to obtain a solution A, comprising: A 1-2 M hydrochloric acid solution was added dropwise to the suspension A to adjust the concentration to 3.5-5.5, and then a surfactant was added. The mixture was stirred at room temperature for 25-35 min to obtain a solution A.

[0010] Preferably, the surfactant is cetyltrimethylammonium bromide, and the addition ratio of cetyltrimethylammonium bromide is 0.9-1.1 g / L.

[0011] Preferably, the hydrothermal reaction temperature is 180-220° C. and the reaction time is 18-24 h.

[0012] Preferably, the suspension is subjected to solid-liquid separation, washing and drying, specifically comprising: The suspension B is filtered 3-5 times, then washed with deionized water and ethanol until neutral, and then dried at 50-70° C. for 10-14 h to obtain the bimetallic catalyst.

[0013] The present invention also provides a bimetallic catalyst, which is prepared by the preparation method of the present invention as described above.

[0014] The present invention discloses an application of the bimetallic catalyst as described above, wherein the bimetallic catalyst is used to degrade xanthate wastewater under visible light.

[0015] The technical solution of the present invention has the following beneficial effects: The preparation method of the bimetallic catalyst of the present invention designs an S-type heterogeneous structure of zinc sulfide and molybdenum sulfide, optimizes the component ratio of the reactants, and synthesizes a nanomaterial showing a nano-scale phenomenon by a solvent thermal method. At the same time, the higher specific surface area and mesoporous structure can provide more active sites, broaden its light absorption range to visible light, and greatly enhance the catalytic effect of the material. Its catalytic rate is twice that of single zinc sulfide. It is applied to the catalytic treatment of xanthate in metallurgical organic mineral processing wastewater, which is of great significance to the green development of mines. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the zinc sulfide / molybdenum sulfide bimetallic catalyst obtained in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the zinc sulfide / molybdenum sulfide bimetallic catalyst obtained in Example 2 of the present invention; Figure 3 This is a scanning electron microscope image of the zinc sulfide / molybdenum sulfide bimetallic catalyst obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0017] According to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structures and implementations. Therefore, the following specific implementation methods and drawings are only examples of the technical solution of the present invention and should not be regarded as the entirety of the present invention or the limitation of its technical solution.

[0018] The preparation method of the bimetallic catalyst provided by the present invention is to prepare a nano ZnS / MeSx heterostructure photocatalytic material by a one-step solvothermal method, thereby broadening the light response range of the material to the visible light region, and improving the light energy utilization rate of the new zinc sulfide-based composite material in xanthate degradation, thereby realizing resource utilization.

[0019] The specific steps of the preparation method of the bimetallic catalyst of the present invention include: Step (1), a certain mass ratio of 1: (3-5): (1-3) ammonium molybdate, sulfur source powder, and zinc acetate are sequentially added to a reaction solvent prepared by mixing ethylene glycol and deionized water in equal proportions. Since the redox potential of molybdenum is positive, the molybdenum ions can first fully contact with the sulfur source to exchange positive and negative ions, and then form a heterojunction with the zinc precursor. Then, ultrasonicate for 10-20 min at an ultrasonic power of 60-80 W to destroy the interaction between molecules to accelerate the dissolution process; then magnetically stir for 1-3 h to make it uniform, provide energy for subsequent chemical reactions and promote the reaction. This step finally obtains suspension A. Among them, the solvent is a solution prepared by mixing ethylene glycol and deionized water in equal volumes, and the mass volume ratio of the total mass of ammonium molybdate, sulfur source powder and zinc acetate to the solvent is (1-1.4):50, in units of g / mL. It should be noted that after equal volumes of ethylene glycol and deionized water are mixed, the volume of the resulting solution is not the algebraic sum of the volumes of the two, but the volume change is not obvious under laboratory conditions. Based on the fact that when preparing the suspension A in the embodiment of the present invention, there is less solid phase and relatively more solvent (sufficient), the volume of the above-mentioned solvent in the embodiment of the present invention is calculated according to the sum of the volumes of ethylene glycol and deionized water.

[0020] Step (2), preparing a 1-2 M hydrochloric acid solution and gradually adding it dropwise to the suspension A of step (1), adjusting the pH value to 3.5-5.5; then adding a cetyltrimethylammonium bromide surfactant to activate the reaction solution, wherein the addition ratio of cetyltrimethylammonium bromide is 0.9-1.1 g / L, and then stirring at room temperature for 25-35 min to obtain a solution A.

[0021] Step (3), transferring the solution A obtained in step (2) to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction to obtain suspension B; the catalyst material synthesized by the hydrothermal reaction has a high specific surface area and an excellent crystal structure while regulating the structure and morphology of the crystal, which can increase the exposure of the active site and the rate of the catalytic reaction. The temperature of the hydrothermal reaction is 180-220 ° C and the time is 18-24 h; The reaction equation is as follows: Zn(CH3COO)2+ CH4N2S = ZnS↓+ 2 CH3COOH 4(NH4)6Mo7O 24 ·4H2O+63CH4N2S+42H2O=150NH3↑+63CO2↑+7H2SO4+28MoS2↓ Step (4), filtering the suspension B obtained in step (3) for 3-5 times, washing with deionized water and ethanol for multiple times until neutral, and then drying at 50-70°C for 10-14 hours to obtain a bimetallic sulfide heterojunction catalytic material and a leachate of acetic acid and sulfuric acid (CH3COOH and H2SO4); The present invention can further reduce the band gap value on the basis of pure zinc sulfide phase to broaden the light response range of the material to the visible light region, and improve the light energy utilization rate of the new zinc sulfide-based composite material in xanthate degradation. Among them, the coupling of two different metals can provide a favorable redox reaction and higher electronic conductivity than single-component sulfide to promote photocatalytic activity, and expand its light absorption range to the visible light range.

[0022] Embodiment 1: The preparation method of the bimetallic catalyst comprises the following steps: Step (1): Weigh 0.3460 g zinc acetate, 0.1730 g ammonium molybdate and 0.5190 g thioacetamide raw materials in a mass ratio of 2:1:3, and respectively measure 25 ml of deionized water and ethanol in equal volumes and mix them as a reaction solvent.

[0023] Step (2): The ammonium molybdate and thioacetamide powders and zinc acetate weighed in step (1) are added to the reaction solvent in sequence, ultrasonicated at a power of 60 W for 10 min, and then magnetically stirred for 2.5 h to make it uniform, to obtain a suspension A.

[0024] Step (3): Prepare a 1 M dilute hydrochloric acid solution and gradually add it dropwise to the suspension A in step (2) to adjust the pH value of the solution to 3.5. The final volume of the solution is 60 ml. Then, hexadecyltrimethylammonium bromide is added to the solution at a solid-liquid ratio of 1.1 g / L. Stir at room temperature for 35 min to obtain solution A.

[0025] Step (4): The solution A obtained in step (3) was transferred to a polytetrafluoroethylene-lined stainless steel autoclave for solvothermal reaction at a temperature of 220°C for 20 h to obtain a suspension B.

[0026] Step (5): The suspension B obtained in step (4) is filtered three times, and washed alternately with deionized water and ethanol until neutral. After solid-liquid separation, the black precipitate is taken out, and then dried at 50°C for 10 h to obtain the bimetallic sulfide heterojunction catalytic material of this embodiment.

[0027] Figure 1 This is a scanning electron microscope image of the zinc sulfide / molybdenum sulfide catalyst obtained in Example 1 of the present invention. It can be seen that the catalyst morphology is a sheet-like structure of nanomaterials, and the high specific surface area and pore structure can provide more active sites.

[0028] 0.06 g of the zinc sulfide / molybdenum sulfide bimetallic catalyst prepared in this example was added to 100 mL of butyl xanthate wastewater with an initial concentration of 50 mg / L. The degradation rate of butyl xanthate was 61.24% under visible light irradiation for 3 h, and it was completely degraded after 4 h.

[0029] Embodiment 2: The preparation method of the bimetallic catalyst comprises the following steps: Step (1): Weigh 0.1730 g zinc acetate, 0.1730 g ammonium molybdate and 0.8650 g thioacetamide raw materials in a mass ratio of 1:1:5, and respectively measure 25 ml of deionized water and ethanol in equal volumes and mix them as a reaction solvent.

[0030] Step (2): the ammonium molybdate and thioacetamide powders and zinc acetate weighed in step (1) are added to the reaction solvent in sequence, ultrasonicated at a power of 70 W for 15 min, and then magnetically stirred for 1 h to make it uniform, to obtain a suspension A.

[0031] Step (3): Prepare a 1 M dilute hydrochloric acid solution and gradually add it dropwise to the suspension A in step (2) to adjust the pH value of the solution to 4.5. The final volume of the solution is 60 ml. Then, hexadecyltrimethylammonium bromide is added to the solution at a solid-liquid ratio of 1 g / L. Stir at room temperature for 30 min to obtain solution A.

[0032] Step (4): The solution A obtained in step (3) was transferred to a polytetrafluoroethylene-lined stainless steel autoclave for solvothermal reaction at a temperature of 200 °C and a reaction time of 24 h.

[0033] Step (5): The suspension B obtained in step (4) was filtered four times, and washed alternately with deionized water and ethanol until neutral. After solid-liquid separation, the black precipitate was taken out, and then dried at 60°C for 12 h to obtain the bimetallic sulfide heterojunction catalytic material of this embodiment.

[0034] Figure 2 This is a scanning electron microscope image of the zinc sulfide / molybdenum sulfide catalyst obtained in Example 2 of the present invention. It can be seen that the catalyst morphology is a microspherical structure of nanoflowers. Compared with the zinc sulfide / molybdenum sulfide catalyst in Example 1, it has better crystallinity and smaller surface energy, and can provide more active sites to improve catalytic activity.

[0035] 0.06 g of the zinc sulfide / molybdenum sulfide bimetallic catalyst prepared in this example was added to 100 mL of butyl xanthate wastewater with an initial concentration of 50 mg / L. The degradation rate of butyl xanthate was 81.16% under visible light irradiation for 3 h, and it was completely degraded after 3.5 h.

[0036] Embodiment 3: The preparation method of the bimetallic catalyst comprises the following steps: Step (1): Weigh 0.5190 g zinc acetate, 0.1730 g ammonium molybdate and 0.6920 g thioacetamide raw materials in a mass ratio of 3:1:4, and respectively measure 25 ml of deionized water and ethanol in equal volumes and mix them as a reaction solvent.

[0037] Step (2): After the ammonium molybdate and thioacetamide powders and zinc acetate weighed in step (1) are added to the reaction solvent in sequence, ultrasonication is performed at an ultrasonic power of 80 W for 20 min, and magnetic stirring is performed for 3 h to make it uniform, thereby obtaining a suspension A.

[0038] Step (3): Prepare a 1 M dilute hydrochloric acid solution and gradually add it dropwise to the suspension A in step (2) to adjust the pH value of the solution to 5.5. The final volume of the solution is 60 ml. Then, hexadecyltrimethylammonium bromide is added to the solution at a solid-liquid ratio of 0.9 g / L. Stir at room temperature for 25 min to obtain solution A.

[0039] Step (4): The solution A obtained in step (3) was transferred to a polytetrafluoroethylene-lined stainless steel autoclave for solvothermal reaction at a temperature of 180°C for 22 h.

[0040] Step (5): The suspension obtained in step (4) is filtered 5 times, and washed alternately with deionized water and ethanol until neutral. After solid-liquid separation, the black precipitate is taken out and then dried at 70°C for 14 h to obtain the bimetallic sulfide heterojunction catalytic material of this embodiment.

[0041] Figure 3 This is a scanning electron microscope image of the zinc sulfide / molybdenum sulfide catalyst obtained in Example 3 of the present invention. It can be seen that the catalyst morphology is an irregular flaky structure. Compared with the zinc sulfide / molybdenum sulfide catalyst in Example 1, it has better crystallinity and poorer adsorption performance for butyl xanthate.

[0042] 0.06 g of the zinc sulfide / molybdenum sulfide bimetallic catalyst prepared in this example was added to 100 mL of butyl xanthate wastewater with an initial concentration of 50 mg / L. The degradation rate of butyl xanthate was 67.23% under visible light irradiation for 3 h, and it was completely degraded after 4.5 h.

[0043] It can be seen from the above scheme that the present invention can broaden the light response range of the material to the visible light region, improve the light energy utilization rate of the new zinc sulfide-based composite material in xanthate degradation, and provide a theoretical reference for the effective degradation and resource utilization of butyl xanthate pollutants.

[0044] The specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a bimetallic catalyst, characterized in that: The process includes the following: Ammonium molybdate, sulfur source powder and zinc acetate are added to a solvent and mixed to allow molybdenum ions and zinc ions to undergo ion exchange to obtain a suspension A; the mass ratio of ammonium molybdate, sulfur source powder and zinc acetate is 1:(3-5):(1-3); the mass volume ratio of the total mass of ammonium molybdate, sulfur source powder and zinc acetate to the solvent is (1-1.4):50, in g / mL; The suspension A is adjusted to be weakly acidic, and then a surfactant is added for activation to obtain a solution A; The solution A is subjected to a hydrothermal reaction to obtain a suspension B; The suspension B is subjected to solid-liquid separation, washing and drying to obtain the bimetallic catalyst.

2. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: The solvent is a solution prepared by mixing ethylene glycol and deionized water in equal volumes.

3. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: After ammonium molybdate, sulfur source powder and zinc acetate are added to the solvent and mixed, the following process is also included: Ultrasonication was performed at an ultrasonic power of 60-80 W for 10-20 min, and then magnetic stirring was performed for 1-3 h to obtain a suspension A.

4. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: The sulfur source powder is thioacetamide.

5. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: The suspension A is adjusted to be weakly acidic, and then a surfactant is added for activation to obtain a solution A, comprising: A 1-2 M hydrochloric acid solution was added dropwise to the suspension A to adjust the concentration to 3.5-5.5, and then a surfactant was added. The mixture was stirred at room temperature for 25-35 min to obtain a solution A.

6. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: The surfactant is hexadecyltrimethylammonium bromide, and the addition ratio of hexadecyltrimethylammonium bromide is 0.9-1.1 g / L.

7. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180-220 °C and the time is 18-24 h.

8. The method for preparing a bimetallic catalyst according to claim 1, characterized in that: The suspension is subjected to solid-liquid separation, washing and drying, specifically comprising: The suspension B is filtered 3-5 times, then washed with deionized water and ethanol until neutral, and then dried at 50-70° C. for 10-14 h to obtain the bimetallic catalyst.

9. A bimetallic catalyst, characterized in that: The bimetallic catalyst is prepared by any one of the preparation methods of claims 1-8.

10. Use of the bimetallic catalyst according to claim 9, characterized in that: The bimetallic catalyst is used for degrading xanthate wastewater under visible light.

Citation Information

Cited By

  • Preparation method and application of modified metal sulfide catalyst for synergistic conversion of acidic natural gas

    CN121422991A